6c-3/3c^2-12
Answer:
36
Step-by-step explanation:
Ok, so the expression we are given is ÷ 3 + 9.
We know that x = 3, so we need to substitute 3 in as x.
So, now the expression looks like ÷ 3 + 9.
Now we can solve this expression.
First we need to figure out what is equal to.
1. = 81
We're left with 81 ÷ 3 + 9.
Next, we need to divide our 81 by our 3.
2. 81 ÷ 3 = 27
Our new expression is 27 + 9.
Last, we need to add our 27 and our 9 together.
3. 27 + 9 = 36
Our answer is 36.
So ÷ 3 + 9 when x = 3 is 36.
Feel free to give brainliest.
Have a great day!
Express your answer in simplest terms.
A. 4 1/4
B. 4 1/8
C. 5 5/8
D. 6 1/4